CONSTRUCTING SOCIAL CRITICISM THROUGH CONNOTATIVE MEANING: A SEMANTIC ANALYSIS OF NAWAL EL-SA‘DAWI’S AL-BANĀT TAʿĪSYŪ - Nurfitriani Romadoni Putri; Ulil Absar (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study aims to analyze connotative meaning as a medium of social criticism in the short story Al-Banāt Ta‘īsyū by Nawal El Sa’dawi. The research uses a qualitative descriptive method with a dilālah (semantic) approach. The study examines one Arabic short story as the main text. Data were collected through reading and note-taking techniques and analyzed through data reduction, data display, and conclusion drawing. The findings show systematic patterns of connotative meaning that function as indirect forms of social criticism. These patterns express criticism of social decline, public suffering, and the oppression of women. In this story, connotative meaning does not only function as a stylistic element but works as a semantic strategy that describes social problems and challenges dominant social ideas in the text. The discussion also reveals several semantic patterns, such as images of social burden, sacrificial metaphors, and the dissolution of women’s identity within collective struggles. The novelty of this study lies in placing connotative meaning as the main analytical perspective for understanding social criticism in modern Arabic short fiction. This research contributes to Arabic literary semantics by showing that connotative meaning can function as an important linguistic tool for expressing ideological criticism in literary texts.